2015
DOI: 10.1177/1535370215619706
|View full text |Cite
|
Sign up to set email alerts
|

Membrane depolarization increases ryanodine sensitivity to Ca2+ release to the cytosol in L6 skeletal muscle cells: Implications for excitation–contraction coupling

Abstract: The dihydropyridine receptor in the plasma membrane and the ryanodine receptor in the sarcoplasmic reticulum are known to physically interact in the process of excitation-contraction coupling. However, the mechanism for subsequent Ca 2þ release through the ryanodine receptor is unknown. Our lab has previously presented evidence that the dihydropyridine receptor and ryanodine receptor combine as a channel for the entry of Ca 2þ under resting conditions, known as store operated calcium entry.Here, we provide evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…However, abnormal and excessive Ca 2+ release from the ER via InsP 3 Rs/RYRs may result in impaired autophagy, mitochondria damage, cell arrest and death [41], which may be the mechanism of some pathology in neurodegenerative diseases [42]. It has been demonstrated that both InsP 3 Rs and RYRs are excessively activated in AD due to abnormally increased receptor numbers [43], and the elevated receptor hypersensitivity to their agonists [44]. Abnormal and excessive Ca 2+ release from the ER not only dangerously increases [Ca 2+ ] c but also detrimentally decreases ER calcium contents.…”
Section: Discussionmentioning
confidence: 99%
“…However, abnormal and excessive Ca 2+ release from the ER via InsP 3 Rs/RYRs may result in impaired autophagy, mitochondria damage, cell arrest and death [41], which may be the mechanism of some pathology in neurodegenerative diseases [42]. It has been demonstrated that both InsP 3 Rs and RYRs are excessively activated in AD due to abnormally increased receptor numbers [43], and the elevated receptor hypersensitivity to their agonists [44]. Abnormal and excessive Ca 2+ release from the ER not only dangerously increases [Ca 2+ ] c but also detrimentally decreases ER calcium contents.…”
Section: Discussionmentioning
confidence: 99%
“…Ryanodine Receptor Activation with Caffeine. Membrane depolarization will uncouple RYR1 from occlusion by the DHPR and allow Ca 2+ release from the SR to the cytosol through the RYR1 channel (Pitake and Ochs 2015); therefore, we determined if HERG affects RYR1 activity specifically. Thus, RYR1 activity was assayed in control and HERG-expressing myotubes using caffeine to activate the RYR1 and the area under the curve (AUC) of the rise in [Ca 2+ ] i was determined for each treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…al., 2004; Lyfenko & Dirksen 2008 in Dirksen 2009). The cells were then depolarized: 1) to release RYR1 from occlusion by Ca v 1.1 (i.e., DHPR) and enable Ca 2+ release from the SR to the cytosol through the RYR1 channel (Pitake and Ochs 2015); and 2) to inhibit SOCE (Stiber et. al., 2008 in Dirksen 2009; Kurebayashi & Ogawa 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 2-APB significantly inhibited ALO-induced increase of IRAP fluorescence intensity at the PM and intracellular Ca 2+ under 2 mM ( Figure 5A ) and 0 mM ( Figure 5B ) extracellular Ca 2+ conditions. In addition to IP 3 R, Ryanodine receptor (RyR) is also an important receptor that regulates intracellular calcium release ( Pitake and Ochs, 2016 ). Therefore, we studied the effect of RyR on ALO-induced intracellular Ca 2+ and GLUT4 trafficking to the PM.…”
Section: Resultsmentioning
confidence: 99%